The genus Blepharella Macquart (Diptera: Tachinidae) in Japan, with notes on the Oriental species B. lateralis Macquart - Shima, Hiroshi; Tachi, Takuji (Zootaxa, 2019)
The genus Blepharella Macquart belongs to the tribe Goniini of the Tachinidae (Diptera). Three new species of this genus are described from Japan (B. bomolocha sp. nov., B. grisescens sp. nov., and B. yaeyamana sp. nov.) and B. nigra Mesnil is redescribed. Blepharella tenuparafacialis Chao & Shi is synonymized with the type species B. lateralis Macquart, syn. nov. and the male and female terminalia of B. lateralis are described and illustrated. The microtype eggs of B. bomolocha, B. nigra and B. lateralis are illustrated for the first time.